2016
DOI: 10.1161/circulationaha.115.018410
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers of Dairy Fat and Risk of Incident Diabetes Mellitus Among Men and Women in the United States in Two Large Prospective Cohorts

Abstract: Background In prospective studies, relationship of self-reported consumption of dairy foods with risk of diabetes mellitus is inconsistent. Few studies have assessed dairy fat, using circulating biomarkers, and incident diabetes. We tested hypothesis that circulating fatty acid biomarkers of dairy fat, 15:0, 17:0, and t-16:1n-7, are associated with lower incident diabetes. Methods and Results Among 3,333 adults aged 30–75 years and free of prevalent diabetes at baseline, total plasma and erythrocyte fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 36 publications
7
101
1
4
Order By: Relevance
“…A meta-analysis of ten large prospective studies found that dietary patterns similar to the AHA dietary recommendations were associated with a 66% reduction in diabetes [39]. Notably, the AHA diet score does not take into account other forms of dietary intake associated with decreases in diabetes and CVD risk including dairy consumption [4042] and glycaemic index/load [4345]. …”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of ten large prospective studies found that dietary patterns similar to the AHA dietary recommendations were associated with a 66% reduction in diabetes [39]. Notably, the AHA diet score does not take into account other forms of dietary intake associated with decreases in diabetes and CVD risk including dairy consumption [4042] and glycaemic index/load [4345]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that regular consumption of whole milk in adults and older people is positively associated with health outcomes, nonetheless neverthe. For example, the use of whole milk has been associated with diabetes control [Yakoob et al, 2016], normal body weight [Vanderhout et al, 2016], reduced risk of ischemic stroke [Elwood et al, 2005], lower risk of coronary disease [Steinmetz et al, 1994] and protection against some types of cancer [Prentice, 2014]. In addition, it has been stated that regularly consuming whole milk induces a rapid and prolonged sensation of satiety, unlike the consumption of skim milk.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the Nurses’ Health Study and the Health Professionals Follow-Up Study show a protective effect of high plasma dairy fatty acid concentrations and lower incidence of diabetes mellitus [34]. …”
Section: Discussionmentioning
confidence: 99%